Correlational Study between Academic Performance, Co-Curricular Activities and Extracurricular Activities in a Select Educational Institution - Gutierrez, Ernell Bautista (Future Science / FSH-PH Publications, 2023)
Academic performance is usually viewed in terms of numerical figures as manifested in the individual activities of students in the classroom. As mentioned by Husaini, Y & Shukor, N (2022), students' Academic Performance is vital for assessing a student's standing within a university. It makes it possible for academic staff, educational administrators, and decision-makers to precisely evaluate students taking various courses throughout a semester. Additionally, it served as a cautionary tale for the students to assess their performance level and make subsequent improvements Supported by the results from the study of Husaini, Y & Shukor, N (2023), students' academic performance is vital for assessing a student's standing within a university. It makes it possible for academic staff, educational administrators, and decision-makers to precisely evaluate students taking various courses throughout a semester. The study investigated the relationship between student’s academic performance and their participation on Co-curricular and Extra-curricular Activities. It further investigated if Age, Sex and Academic Program would cause significant differences in their Academic Performance, Co-curricular Activities and Extra-curricular Activities. A total of 75 students from the Business Administration program participates in the study. The students were from the four (4) academic majors namely; Marketing Management, Financial Management, Operation Management and Human Resource Management. Results revealed that Co-curricular Activities and Extra-curricular Activities of the students are both significantly related to their academic performance with P-value < 0.05. Likewise, the Age, Sex and Academic Program of the students did not cause any differences on their assessments towards Academic Performance, Co-curricular Activities and Extra-curricular Activities with P-value of >0.05.